(untitled) (Research, Society and Development, 2021)
Cervicogenic headache has a complex and poorly understood pathophysiology. Symptoms are typical and involve the C2 and C3 nerve roots. There are no specific recommendations for physical therapy, although occipital nerve block is a known pharmacological treatment. Some evidence suggests that hip rotation correction could aid in reducing cervical pain symptoms. The objective of this work is to evaluated the role of postural physiotherapy for hip rotation correction using the Maitland technique in patients with cervicogenic headache who underwent an occipital nerve block. In this retrospective, observational and uncontrolled study, patients were evaluated from January 2017 to February 2018. After diagnosis of cervicogenic headache they underwent anesthetic block, hip radiography with lower limb scanometry and cervical tomography, after which they were referred to physical therapy. The analog pain scale was used for evaluation at the time of diagnosis and after the proposed physiotherapy. Patients submitted to an occipital nerve block were divided into three groups: Group I (n = 15, physical therapy with Maitland technique) had an analog pain score of 1.6 after the physical therapy, Group II (n = 11, conventional physiotherapy) had an analog pain score of 3.7 after the physical therapy and Group III (n = 13, occipital nerve block only) had an analog pain score of 5.2 after the occipital nerve block. The results suggest that an occipital nerve block in combination with the Maitland technique is superior in patients with cervicogenic headache compared to nerve block only or blockade combined with non-specific physical therapy (p=0,013).